Parental cigarette smoking, transforming growth factor-alpha gene variant and the risk of orofacial cleft in Iranian infants - Asghar Ebadifar; Roya Hamedi; Hamid Reza KhorramKhorshid; Koorosh Kamali; Fatemeh Aghakhani Moghadam (Iranian Journal of Basic Medical Sciences, 2016)
Objective(s):We investigated the influence of genetic variation of the transforming growth-factor alpha (TGFA) locus on the relationship between smoking and oral clefts. Materials and methods:In this study 105 Iranian infants with non-syndromic cleft lip/palate and 218 controls with non-cleft birth defects were examined to test for associations among maternal exposures, genetic markers, and oral clefts. Maternal and parental smoking histories during pregnancy were obtained through questionnaire. DNA was extracted from newborn screening blood samples, and genotyping of the BamHI polymorphism in the TGFA gene was performed by polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP) methods. A number of factors including gender of the newborns, type of oral cleft, consanguinity of the parents, as well as the mother’s age and education were evaluated as potential confounders and effect modifiers. Results: Maternal smoking, in the absence of paternal smoking, was associated with an increased risk for CL/P (OR = 19.2, 95% CI = [(6.2-59.5)])   and cleft palate only (OR =48.7, 95% CI = [(8-29.3)]). If both parents smoked, risks were generally greater (OR = 55.6, 95% CI = [12-20.25]). Analyses for the risk of clefting from maternal smoking, stratified by the presence or absence of the TGFA/BamH1variant, revealed that the risk of clefting among the infants with the TGFA/BamH1 variant when their mothers smoked cigarettes was much greater than the infants who had non-smoker mothers (P=0.001, OR=10.4,95% CI=[3.2,33.6]). Conclusion:The results of this study indicate that first-trimester maternal smoking and infant TGFA locus mutations are both associated with nonsyndromic cleft lip and/or palate (CL/P).